Heterogeneity of prevalence and risk factors for Active Convulsive Epilepsy in a rural district of Kenya - Edwards, T (2008)
BACKGROUND: There are few large-scale studies of epilepsy in sub-Saharan Africa. We estimate the prevalence, treatment gap and risk factors for active convulsive epilepsy (ACE) in Kenyans aged ≥6 years in a rural area. METHODS: A three-phase screening survey of 151,408 individuals followed by a nested community case-control study. FINDINGS: The overall prevalence of ACE was 2.9 per 1000 (95%CI: 2.6 to 3.2 per 1000) and after adjustment for non-response and sensitivity, 4.5 per 1000 (95%CI; 4.1 to 4.9). There was substantial heterogeneity in the prevalence, with evidence of clustering. The treatment gap was 70.3% (95%CI: 65.9 to 74.5) with weak evidence of a difference in sex and residential division. Adjusted odds of ACE for all ages were increased for family history of non-febrile convulsions (OR 3.3, 95%CI: 2.4 to 4.7), family history of febrile convulsions (OR 14.6, 95%CI: 6.3 to 34.1), history of both seizure types (OR 7.3, 95% CI: 3.3 to 16.4) and previous head injury (OR 4.1, 95%CI: 2.1 to 8.1). In multivariable analyses in children, adverse perinatal events increased odds (OR 5.7, 95%CI: 2.6 – 12.7) as did paternal orphanhood (OR 5.1, 95%CI 2.4 to 11.0). INTERPRETATION: This survey demonstrates significant heterogeneity in the prevalence of ACE in large population in Africa and identifies subgroups in greatest need of targeted interventions through assessment of prevalence, treatment adherence and demographic variation in screening response. Adverse perinatal events, febrile illness and head injury are potentially preventable risk factors of epilepsy in this region.